Semantics of sentences with participles (Eurasian Journal of Philology Science and Education, 2021)
The article discusses the problems of teaching the participles of the Kazakh language. There are several reasons for this. Firstly, in modern Kazakh linguistics, not all theoretical issues of the participle have been investigated. For example, the grammatical status of the participles in the Kazakh language still causes scientific discussion. Secondly, the functions of the participles in speech and the linguistic definition proposed in the textbooks are significantly different from each other. The relevance of the study is determined by the fact that the functional study of the participial constructions of the language system as a result of cognitive activity is one of the important tasks of the linguistic description of the Kazakh language in order to teach the Kazakh language as a second. The task of describing the functioning of adverbial revolutions from a cognitive point of view was to determine and explain exactly what relation is recorded by the adverbial revolution, which knowledge structures are behind it. In this article, for the first time, a specific object of research was the identification of the frequency of compatibility of verbs of different vocabulary-semantic groups with participles and the definition of a cognitive model of this grammatical category. . The results of the study showed that the semantic relations of the main verb and participles are ambiguous. The nature of the relationship between these two forms is determined by the general proposition of the utterance. With the dynamic nature of the attitude, vocabulary and semantic characteristics of the main verb are of great importance.